Re-imagining Digital Transformation in the United States: Harnessing Artificial Intelligence and Business Analytics to Drive IT Project Excellence in the Digital Innovation Landscape - Faruq, Omar; Islam, Md Iftakhayrul; Islam, Md Samirul; Tarafder, Md Tanvir Rahman; Rahman, MD Masudur; Islam, Md Saiful; Mohammad, Nur (Journal of Posthumanism, 2025)
The digital transformation in the United States is at a critical crossroads, influenced by the integration of artificial intelligence (AI), business analytics (BA), and the quest for IT project excellence. In contrast to previous digitization efforts that emphasized efficiency, the current transformation is strategic, systemic, and value-oriented, addressing national priorities including economic competitiveness, cybersecurity, sustainability, and equity. This study contends that AI and BA function as complementary facilitators of this transformation: AI automates processes, improves decision-making, and stimulates creativity, whilst BA supplies the analytical foundation for evidence-based strategies, workforce optimization, and stakeholder alignment. They redefine IT project excellence as a multifaceted concept that encompasses efficiency, adaptability, security, and social responsibility.